2004
DOI: 10.1007/bf03395477
|View full text |Cite
|
Sign up to set email alerts
|

Near-Miss Effects on Response Latencies and Win Estimations of Slot Machine Players

Abstract: The present study examined the degree to which slot machine near-miss trials, or trials that displayed 2 of 3 winning symbols on the payoff line, affected response times and win estimations of 12 recreational slot machine players. Participants played a commercial slot machine in a casino-like laboratory for course extra-credit points. Videotaped sessions were later coded to assess trial types and participant response latencies and win estimations for each participant. Results show that all 12 participants emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…Therefore, it seems likely that increasing the time period between bet outcome and initiation of another bet on other types of gambling tasks, on which it has been shown that losing (i.e., punishing) trials result in faster initiation of the start of the consecutive trial (i.e., faster betting) than winning trials (e.g., video poker simulations (Dixon & Schreiber, 2002) and slot machines (Dixon & Schreiber, 2004;Schreiber & Dixon, 2001), should moderate maladaptive gambling behaviour in a similar manner to that demonstrated on the pause version of the CP task in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems likely that increasing the time period between bet outcome and initiation of another bet on other types of gambling tasks, on which it has been shown that losing (i.e., punishing) trials result in faster initiation of the start of the consecutive trial (i.e., faster betting) than winning trials (e.g., video poker simulations (Dixon & Schreiber, 2002) and slot machines (Dixon & Schreiber, 2004;Schreiber & Dixon, 2001), should moderate maladaptive gambling behaviour in a similar manner to that demonstrated on the pause version of the CP task in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Using the dual-monitor system with the software described by MacLin et al (1999), one can easily manipulate other factors present in a casino environment, such as display types, sounds from the slot machine, and number of payoff lines. Future research might also examine some of the important components within the slot machine simulation itself, such as the near miss (Dixon & Schreiber, 2004), auditory feedback, and the perceived ability to exert control over the slot machine outcome. If we can predict responding on slot machines of recreational gamblers, we might be on the road to better understanding the variables that contribute to excessive, pathological gambling.…”
Section: Discussionmentioning
confidence: 99%
“…The program is based on a version of a slot machine created in Visual Basic.NET by one of the authors (MacLin et al, 1999). The program has been modified to run on a computer supporting dual monitors (see Figure 1) and to accept graphics from Internet-based gambling sites (Dixon & Schreiber, 2004). For example, sounds and graphics can be downloaded and applied as "skins" to the existing program.…”
Section: Methodsmentioning
confidence: 99%
“…both entail the loss of the initial bet). Using a commercial slot machine, players rated near-misses as being 'closer to a win' than full-misses (Dixon and Schreiber 2004) (see also Belisle and Dixon 2015;Dymond et al 2014). A group of video lottery players whose games were interspersed with near-misses played longer than a group with no near-misses (Côté et al 2003).…”
Section: Introductionmentioning
confidence: 99%